Penilaian Walkability Index Jalur Pejalan Kaki di Kawasan Kota Lama Semarang - Kurnianingtyas, Agnesia Putri; Dahnyanto, M Faiz Luthfi (Institut Teknologi Nasional Yogyakarta, 2023)
The Semarang Old City area is a historical tourist area and urban public space in Semarang City which has undergone revitalization. This revitalization has had an impact on increasing social and economic activity and supporting tourist arrivals, making pedestrian paths play a crucial role because they are part of the activities in the Old City area. Providing quality pedestrian paths is one of the needs that must be met to increase user comfort, considering that the revitalization of the Old City also carries the concept of walkable tourism where tourists are invited to enjoy the beauty of the Old City on foot. This research aims to assess the quality of pedestrian paths in the Kota Lama area by measuring the Global Walkability Index (GWI) which consists of 9 parameters. This research uses a quantitative descriptive method by comparing the existing conditions of pedestrian paths in Kota Lama with the GWI assessment standards. Apart from that, visitors were also assessed by distributing questionnaires to determine visitors' perceptions of the quality of existing pedestrian paths. The sample from this research was 96 respondents who were divided into 6 segments where sample selection used the stratified random sampling method. Based on the results of the analysis, it was found that the level of walkability of pedestrian paths in the Old City area based on observation results was 61.8 and based on user perceptions it was 62.4. This score is included in the score classification of 60-79, indicating that in Kota Lama there are complete and comfortable pedestrian facilities so that most activities can be carried out on foot. Improving the quality of pedestrian paths can be done by referring to GWI parameter values that are still below average, such as conflicts between pedestrian paths and other modes of transportation, the availability of crossing facilities and infrastructure for people with disabilities. Apart from that, development is also carried out on parameters that are deemed to need improvement according to existing conditions, such as security parameters against crime and the availability of supporting facilities.